Platform Externality, Asymmetric Information, and Counterfeit Deterrence in E-Commerce. Issue 14 (14th November 2018) - Miao, Qi; Xie, Danxia; Zhong, Weiqiang
ABSTRACT: The fight against online sales of counterfeit goods has received much attention. To the best of our knowledge, existing literature on online counterfeiting lacks a theoretical framework. To fill this gap, this article proposes a two-period model with sellers, buyers, and a platform. We focus on the relationship among platform structure (characterized by the ratio of buyers to sellers), asymmetric information, deterrence strength, and the ratio of counterfeits. Cross-network externalities of platform make platform managers worry about potential exodus of buyers and sellers due to counterfeits. This externality provides platform with strong incentives to fight counterfeits by itself, even without external regulatory requirement. We further show that the higher the ratio of buyers to sellers, the lower the ratio of counterfeits. Moreover, a lower degree of information asymmetry or a higher degree of punishment can reduce the ratio of counterfeits. We suggest that governments and e-commerce platforms work together in the fight against counterfeiting.